Model of Independent Activity Learning Unit (UKBM) in Macromolecular Learning to Train The Cognitive Ability and Creativity of Vocational High School Students - Khasanah, Rohmatul; Saptono, Sigit (Journal of Environmental and Science Education, 2022)
This study aims to develop and analyze the characteristics and validity of the Independent Activity Learning Unit (UKBM) model in learning Macromolecules because of its development to train the cognitive abilities and creativity of vocational high school students. The type of research used is Sugiyono's modified R&D with six steps of development research. The trial step could not be carried out due to Covid-19 constraints. The subjects of this development research were five validators, material experts, and media experts. UKBM validity was obtained from the validator's assessment through a validation sheet using a Likert scale. The results showed that after being validated and revised based on suggestions from the validator, the results of the first study showed that the UKBM developed had the characteristics: according to on basics competence (KD), measure competency achievement, utilizes learning technology, easy to apply, develops HOTS but cannot be separated from LOTS, and 6) attractive appearance. Then, the validity of the UKBM developed by the material validator is 84.66%, which indicates that the UKBM developed is valid, and 88.4% by the media validator, which indicates the UKBM developed is very valid